Push And Pull Factors for People Living in the Mountains of Arfak in Manokwari City - Mulyadi Mulyadi (Green Publisher Indonesia, 2022)
This study aims to determine 1) the characteristics of the people of Arfak who migrated to the city of Manokwari ; 2) the driving factors for the migration of the Arfak people from their home villages, and 3) the pull factors for the migration of the Arfak people to the city of Manokwari . To obtain data, the study used a descriptive approach through survey activities to the Arfak community living in the city of Manokwari as a case. The case of this research is the mobility or migration of the Arfak community as the main ethnic group in Manokwari Regency. The results showed that the main driving force behind Arfak mountain residents leaving their villages was economic factors, namely in their home villages they did not have adequate educational facilities, limited employment opportunities only relied on agriculture and forest labor, transportation and communication facilities were still lacking , the price of goods was limited. basic necessities are expensive, and the fear of being attacked by suanggi . Meanwhile, the issue of differences of opinion within the church, land disputes, and cold weather conditions do not always have an effect. While the main pull factor so that Arfak residents are interested in moving to the city of Manokwari are because the reasons in the city are good health and education facilities and services, available jobs, easy access to government, and guaranteed security.